ANALISIS KEBIJAKAN BAWASLU PROVINSI SULAWESI TENGGARA DALAM PELAKSANAAN PROTOKOL KESEHATAN PADA PILKADA SERENTAK TAHUN 2020 - Eka Suaib; La Ode Mustafa R; Nurdin Iskandar (Journal Publicuho, 2023)
This study aims to identify and analyze the Oversight Policy of the Election Supervisory Board for Southeast Sulawesi Province in implementing the COVID-19 health protocol in the simultaneous regional head elections in 2020. This study used a qualitative approach with 12 informants selected by purposive sampling technique. The data in this study were obtained through interviews and documentation, then the data obtained was analyzed qualitatively with an interactive model consisting of data reduction, data presentation and drawing conclusions. The results of this study indicate that the supervision policy of the General Election Supervisory Board of Southeast Sulawesi Province in implementing the COVID-19 health protocol in the 2020 Simultaneous Regional Head election refers to the regulation of the General Election Supervisory Agency of the Republic of Indonesia Number 4 of 2020 which explains the policy of providing protocol facilities and infrastructure health in every Pilkada activity, policies to protect the safety of election administrators, participants, voters, and other parties involved with Pilkada activities and policies to increase public participation in regional head elections. Increasing community participation is very important in holding regional head elections because the community as voters has a large enough share in determining the winning candidate pair in the election process.